Unstructured Socializing with Peers, Low Self-Control, and Substance Use - Leimberg, Anna (International journal of offender therapy and comparative criminology, 2022)
Research consistently finds that unstructured socializing with peers and low self-control are both positively associated with substance use among adolescents. However, largely absent from the literature is a consideration of whether unstructured socializing with peers and low self-control have differential and interactive effects when predicting usage of different classifications of drugs. The current study addresses these issues using data collected on a statewide sample of middle school and high school students who participated in the 2017 Florida Youth Substance Abuse Survey. Results indicate that (1) unstructured socializing with peers is a stronger predictor of soft drug use than low self-control, (2) low self-control is a stronger predictor of hard drug use than unstructured socializing with peers, and (3) the effect of unstructured socializing on both soft and hard drug use is diminished among adolescents who are lower in self-control.